DAMPAK BILINGUAL TERHADAP PERKEMBANGAN KOGNITIF ANAK SEKOLAH DASAR - Kanisius Kami (SekolahTinggi Keguruan dan Ilmu Pendidikan (STKIP), 2017)
Bilingualism is closely related to the acquisition of a second language. Language acquisition is closely related to how children acquire words, meanings, structures, and pragmatics. It is nothing else related to the processes that occur in the mind and attitude of the child. In the era of globalization, the mastery of foreign languages, especially English as an international language, is mandatory. Currently in Indonesia, English is taught in primary schools and even in early childhood education. This article discusses children's learning, especially in terms of cognitive psychology in learning foreign languages as a second language. The method used is literature study and data collection is analyzed descriptively. It is important to note that the cognitive development of primary school children is appropriate for language learning and there are advantages to learning foreign languages in primary schools. In addition, bilingual people are more profitable than monolingual people. Keywords: Bilingual, Cognitive Development, Impact